Study on Acne Scarring and Its Relationship between Severity and Treatment of Active Acne: An Observational Study (Journal of Current and Advance Medical Research, 2023)
Background: Incorrectly selected treatment or the presence of severe acne vulgaris can lead to the formation of atrophic scars.Objective: The purpose of the present study was to evaluate the acne scarring and its relationship between severity and treatment of active acne.Methodology: This was cross-sectional observation study was performed in the EW VM Health Bangladesh Ltd., Dhaka for a period of 6 months. Evaluation of the types, sites, and severity of acne scars was done, and details of the severity and treatment of acne were recorded. Patients of all age-groups presenting for treatment of acne scars were included in the study.Results: This study shows maximum (40%) were age group 31-40 years. Face was involved in all the patients with acne vulgaris, which included the cheeks (91%), forehead (43%), jaw (51%), chin (27.0%), and nose (16.0%). The most common type of lesion predominantly observed was comedones (54.0%) followed by papules (53.0%), pustules (43.0%), nodules (29.0%), and cysts (3.0%). It was observed that 21.0% were mild acne, 27.0% were moderate acne and 52.0% severe acne. In grading system of acne scaring, 19.0% were macular acne scar, 14.0% were mild acne scar, 28.0% were moderate acne scar and 39.0% were severe acne scar.Conclusion: This study found majority of patients with active acne delay treatment, which leads to increased acne scarring.Journal of Current and Advance Medical Research, July 2022;9(2):69-73